2011
DOI: 10.1007/s10584-011-0373-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of local anthropogenic and regional climatic transient signals in temperature logs from Czechia and Slovenia

Abstract: The paper reports on detection and quantification of the impact of local anthropogenic structures and regional climatic changes on subsurface temperature field. The analyzed temperature records were obtained by temperature monitoring in a borehole in PragueSpořilov (Czechia) and by repeated logging of a borehole in Šempeter (Slovenia). The observed data were compared with temperatures yielded by mathematical 3D time-variable geothermal models of the boreholes' sites with the aim to decompose the observed trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…For example, Ampofo et al (2006) used numerical models to investigate the heat-load of an underground railway, whereas the heat absorbed by the earth surrounding a subway can reach up to 30% of the total heat generated by the structure. Dědeček et al (2012) showed that the present subsurface temperature field observed and monitored at two locations in Central Europe (Prague-Spořilov/Czechia and Šempeter/Slovenia) is strongly influenced both by recent regional climatic changes and by thermal effects from local anthropogenic structures. With 3D numerical simulations in transient geothermal models, they could separate the transient signals of the two sources and show that they are of a similar magnitude at the two sites they studied.…”
Section: Introductionmentioning
confidence: 80%
“…For example, Ampofo et al (2006) used numerical models to investigate the heat-load of an underground railway, whereas the heat absorbed by the earth surrounding a subway can reach up to 30% of the total heat generated by the structure. Dědeček et al (2012) showed that the present subsurface temperature field observed and monitored at two locations in Central Europe (Prague-Spořilov/Czechia and Šempeter/Slovenia) is strongly influenced both by recent regional climatic changes and by thermal effects from local anthropogenic structures. With 3D numerical simulations in transient geothermal models, they could separate the transient signals of the two sources and show that they are of a similar magnitude at the two sites they studied.…”
Section: Introductionmentioning
confidence: 80%
“…2a). It was drilled through Quaternary clay, sand and gravel in the first 16 m, below which lies Miocene marl, which gradually becomes more clayey with depth (Rajver et al, 2006;Šafanda et al, 2007;Dědeček et al, 2013). In Figure 2a the last temperature log from August 30 th , 2011 is also presented.…”
Section: Methodology Of Temperature Measurements In the Borehole V-8/mentioning
confidence: 99%
“…Due to high specific heat of pore water, it could be as low as 0.4 • 10 6 m 2 /s (for 30 % total porosity) (Šafanda et al, 2007). Dědeček et al (2013) extracted thermal diffusivity from subsurface temperature data at Malence. They got 0.2 -0.3 • 10 -6 m 2 /s in the top 5 to 10 cm of soil and 0.5 -0.7 • 10 -6 m 2 /s within 0.1 to 10 m of the bedrock.…”
Section: Methodology Of Temperature Measurements In the Borehole V-8/mentioning
confidence: 99%
See 1 more Smart Citation
“…General groundwater flow directions are indicated by arrows (dark blue). (Davis et al, 2010;Dědeček et al, 2012;Harris & Chapman, 2007) or the effects of urbanization (Ferguson & Woodbury, 2007) or land use (Kooi, 2008;MacDougall & Beltrami, 2017) on subsurface temperatures.…”
Section: Introductionmentioning
confidence: 99%